Fakakoloa as embodied mana moana and agency: Postcolonial sociology within Oceania - Fa‘avae, David Taufui Mikato; Fehoko, Edmond; Vaka, Sione (New Zealand Sociology, 2026)
The coupling of mana moana is grounded in inspiration from and through Indigeneity and Moana sense-making (intimate understanding through our sensibilities within Oceania). Tongan meaning-making is centred on talanoa-vā, a framework that begins theorisation and analytical unpacking from an Indigenous Moana relational vantage point. We employ talatalanoa (ongoing conversations) to story and capture our conceptualisations of fakakoloa (purposefully sharing and imparting knowledge) and mana moana across interdisciplinary intersections as Tongan male educators and researchers working across the social sciences and health sciences. Our unpacking of mana moana as collective agency and responsibility is a feature of being located in tu‘atonga (outside of Tonga; also relates to the Tongan diaspora). Fronting and centring Tongan thought and concepts is our way of grounding relational sense-making in Aotearoa/New Zealand whenua (places). Sociological inquiry through decoloniality within the postcolonial era from a Moana vantage point relies on approaches like talanoa-vā and talatalanoa to disrupt the normalised conditions and traditions of thinking and theorising within Euro-American-centric academe.